2020
DOI: 10.1177/1077801220920378
|View full text |Cite
|
Sign up to set email alerts
|

Same-Sex Couples and the Police: A 10-Year Study of Arrest and Dual Arrest Rates in Responding to Incidents of Intimate Partner Violence

Abstract: Despite concern, little research has been conducted on whether victims in same-sex relationships receive disparate treatment from law enforcement. Utilizing 2000 through 2009 National Incident-Based Reporting System data, the authors examine the police response to incidents involving same-sex and heterosexual couples in 2,625,753 cases across 5,481 jurisdictions in 36 states and Washington, D.C. Results show that incidents with same-sex couples are less likely to result in arrest, but far more likely to result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 74 publications
(116 reference statements)
1
2
0
Order By: Relevance
“…In other instances of IPV, the couple was simply threatened with dual arrest due to the inability of officers to correctly determine the identity of the perpetrator. This tendency is consistent with a recent analysis that revealed disparate outcomes for IPV events between same-sex romantic partners, as officers were significantly more likely to enact dual arrests relative to IPV between heterosexual couples (Hirschel and McCormack 2020). In one such instance, Andy, a 24-year-old lesbian, called the police after being choked by her partner.…”
Section: The Impact Of Lgbtq Identities On Interactions With Policesupporting
confidence: 89%
“…In other instances of IPV, the couple was simply threatened with dual arrest due to the inability of officers to correctly determine the identity of the perpetrator. This tendency is consistent with a recent analysis that revealed disparate outcomes for IPV events between same-sex romantic partners, as officers were significantly more likely to enact dual arrests relative to IPV between heterosexual couples (Hirschel and McCormack 2020). In one such instance, Andy, a 24-year-old lesbian, called the police after being choked by her partner.…”
Section: The Impact Of Lgbtq Identities On Interactions With Policesupporting
confidence: 89%
“…This may be in part because police tended to see two people of the same gender as equals in the relationship (Frierson, 2014; Hereth, 2021; Walker, 2021). However, there was conflicting evidence regarding whether abuse in same‐gender couples is overall less likely to result in arrest (Hirschel & McCormack, 2021; Messing et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Differences in rates of IPV among SMW may be explained in part by demographic factors. Hirschel and McCormack (2021) analyzed more than 2.5 million cases of IPV reported to law enforcement in the United States and found that female–female couples involved in these incidents were significantly younger than male–male and male–female couples. Steele et al (2020) and others (Barrientos et al, 2018; Descamps et al, 2000) found that SMW who report IPV tend to have lower income and educational levels.…”
Section: Resultsmentioning
confidence: 99%